PENGARUH UKURAN DEWAN KOMISARIS DAN KOMITE AUDIT TERHADAP MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2013 - 2015 - Rita Aprilliani; Aloysius H. (Fakultas Ekonomi Dan Bisnis, Universitas Mercu Buana, Jakarta, 2017)
This study aims to know the influence of board commissioners size and audit committee to earning management practices. Objects in this study are a Manufacturing Company Listed in Indonesia Stock Exchange. This study using purposive sampling method. Data collection method used is the method of documentation. Processing data using Eviews program version 7. The results of data analysis used statistical analysis in the form of multiple linear regression. The results of this study indicate that simultaneously all independent significantly influence on earnings management and audit committee in partial not impact on earnings management whereas the size of the board commissioners significant negative on earnings management. This is evidenced by the results of simultaneous test (F test) and the results of the partial test (t test) demonstrated the significant value of these two variables to support and reject the hypothesis.